Message Distortion Potential of Tsunami Early Warning System in Southern Java - Damayanti Wardyaningrum; Endang Ripmiatin (UniversitasAl Azhar Indonesia, 2025)
Many tsunami events that have occurred in Indonesia have been published and also indicate the need for more adequate disaster mitigation efforts. One appropriate disaster mitigation measure is the use of an early warning system. Several studies have found that early warning systems do not work when tsunamis occur. This study aims to identify problems in the implementation of the tsunami early warning system in Indonesia from the perspective of the concept of distortion in communication messages. The research uses qualitative approaches supported by previous studies, various government regulations and supporting data from interviews with residents and tsunami early warning system managers. The research found that the potential for message distortion in communication in early warning systems is grouped into three categories. First, message distortion potential can arise from the operation of tsunami early warning system equipment. Second, message distortion may occur due to coordination in the management of the early warning system. Thirdly, message distortion may arise due to the perception of residents regarding their knowledge of the early warning system. This research recommends eliminating potential message distortion in tsunami early warning system communication by simplifying the flow of the early warning system to shorten coordination among system managers.Keywords: Distortion, Early Warning System, Message, Tsunami.